1988
DOI: 10.1007/bf02371555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term flooding on growth, yield and mineral composition of wheat on sodic soil under field conditions

Abstract: In sodic soils of the Indo-Gangetic alluvial plains of Northern India, flooding for short periods often occurs during the growing season of wheat, leading to low yields. A field study was therefore conducted to evaluate the effects of short-term flooding on growth, yield and mineral composition of wheat (Triticum aestivum Linn. emend. Fiori and Paol) in a sodic soil (pH 8.9, exchangeable sodium percentage 25). Flooding wheat for 2, 4 and 6 days at the time of first irrigation (25-day old plants), significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…Similar adverse effect of salinity on plant height was also reported by Kingsbury and Epstein (1904). Zehid et al (1986), Singh and Rana (1987) and Sharma and Swarm (1987). Table 2 presents data concerning number of tillers plantG 1 .…”
Section: Methodssupporting
confidence: 81%
“…Similar adverse effect of salinity on plant height was also reported by Kingsbury and Epstein (1904). Zehid et al (1986), Singh and Rana (1987) and Sharma and Swarm (1987). Table 2 presents data concerning number of tillers plantG 1 .…”
Section: Methodssupporting
confidence: 81%
“…In both plants, Na + accumulation in the plant did not reach a seriously toxic level since in a previous study (Matsuura et al, 2005) in the plants accumulating much more Na + . Sharma and Swarup (1988) reported that short-term fl ooding in the fi eld increased the Na + concentration in the shoots and roots of wheat but the concentration did not reach toxic levels. They therefore concluded that the reduced growth and yield under excess moisture conditions was not due to ion toxicity but to the reduced uptake of nutrients.…”
Section: Accumulation Of Kmentioning
confidence: 99%
“…Even short term flooding for 2-6 days in sodic soil may cause grain yield reduction of 17-47 % [3]. Wheat production could likely be improved in waterlogged sodic soil by growing waterlogging tolerant genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…these soils become anoxic with redox potential \?350 mV [2]. In India, 2.5 million ha of alkaline soils of Indo-Gangetic plains planted with wheat may experience saturated or temporary waterlogged conditions every year due to excess rains or mismanagement of water drainage from the farmer's field [3].…”
Section: Introductionmentioning
confidence: 99%